Development of directional responses to sounds in the rat (Rattus norvegicus) - Potash, M; Kelly, J (Journal of comparative & physiological psychology, 1980)
The first of two experiments was carried out to examine the tendency of rat infants (13-20 days of age) to approach auditory stimulation. Tests were conducted in a circular maze with a central start area and eight response areas at the periphery. Stimuli were played back over a loudspeaker placed behind one of the eight response areas. Signals included species calls at high and low intensities. A control condition with blank tapes was also used. The subjects showed a clear tendency to approach the low-intensity playback of a species "social" vocalization but did not approach the other stimuli. The aim of the second experiment was to investigate the importance of binaural cues for localization. Rat infants were tested with one ear blocked, both ears blocked, or neither ear blocked. The effect of the ear plug(s) was to attenuate the sound approximately 10 dB. The results indicated that only the binaurally blocked and normal control subjects approached the sound source at above chance levels. The failure of subjects in the monaural group to approach the sound probably resulted from a disruption of binaural cues. The ability of rat infants to localize sounds and process binaural cues is discussed in relation to the onset of hearing and in terms of physiological response that are present early in ontogeny.